PERSEPSI PEDAGANG PASAR TERHADAP PROGRAM ERLINDUNGAN PASAR TRADISIONAL OELH PEMERINTAH KOTA SEMARANG Setudi Kasus Pedagang Pasar Peterongan Semarang Selatan - Priytno Harsasto; Puji Astuti (Journal of Politic and Government Studies, 2013)
ABSTRACTAlong with the development of business scale and the sharpening of competition in thebusiness world growing needs of the community as well. Traditional market in Indonesiacontinues to try to survive the attack of the modern market. Government has theresponsibility to implement the protection of traditional traders tersebutkarena welfare rightsare part of the economic rights to be one right dalamkovenan social economic and culturalrights. The unit of analysis in the study is the traditional market traders who opened hisbusiness in the Market Peterongan. Collection techniques used observation, documents andquestionnaires. Analysis of the data compiled in the frequency of symptoms then describedby the object under study. The results showed traders perception of the traditional marketprotection program by the City of Semarang includes not good. Traders feel that theprotection of traditional markets by the City of Semarang appropriate Minister of TradeRegulation No. 53/M-DAG/PER/12/2008 on Guidelines for Planning and Development ofTraditional Markets, Shopping Centers and Stores Modern in Semarang City has not gonewell. Local governments and managers of traditional markets, particularly the City ofSemarang and Peterongan market manager, suggested significantly invest in theimprovement of traditional markets and establish minimum service standard